Energy demand and vehicle emissions stimate in Aburra Valley from 2000 to 2010 using LEAP model (2015)
This article shows a retrospective analysis of energy demand and atmospheric pollution by urban transport in Aburrá Valley, where Medellín is the main city. The study was carried out using LEAP model between 2000 and 2010, in order to generate information for defining strategies to help reduce air pollution in Aburrá Valley. The results show that despite the rapid increase of vehicles, the energy demand and CO2 emissions grew slowly, while criteria pollutant emissions decreased during the last decade. Also, the study shows that during the modeled period trucks were an important source of CO, NOX, SOX and PM2.5. Motorcycles (2-cycles) were also important contributors to VOC vehicular emissions.